PENINGKATAN PRODUKTIVITAS PERUSAHAAN DENGAN MEREDUKSI AKTIVITAS DAN PEMBOROSAN (WASTE) PADA PROSES PRODUKSI - Amin, Fatkhul (Dinamika Ekonomi, 2004)
A production process is the main activity of a transformation processs from input into output that determines the quality of the product. The quality of product is an absolute component to maintain the company's perpetuation.  Considering the tight conpetition in this global trade era. The improvement in all side should be done continuously to achieve the purpose of the company: producing a qualified product rapidly qualified as well as can be offered at a competitive price. So that, the product will be marketable. The improvement of human resource's knowledge and skill is one of the strategies in improvement to gain the goal of the company. Keyword: a production process, the quality of product